Extreme-QTL mapping of monepantel resistance in Haemonchus contortus. - NICIURA, S. C. M. (2019)
Haemonchus contortus, a gastrointestinal nematode parasite of sheep, is mainly controlled by anthelmintics; the occurrence of anthelmintic resistance leads to treatment failures and increases economic burden. Because molecular mechanisms involved in drug resistance can be elucidated by genomic studies, an extreme quantitative trait locus (X-QTL) mapping approach was used to identify co-segregation of the resistance phenotype with genetic markers to detect the genome-wide variants associated with monepantel resistance in H. contortus.